Metacognition Research Trends in Physics Education: A Systematic Literature Review with Flavel’s Metacognition Framework - Wicaksono, B. Anggit; Purwaningsih, Endang; Diantoro, Markus; Sunaryono, Sunaryono (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2025)
Even though reviews related to metacognition in education have been reported periodically, reviews of metacognition in physics education have rarely been explored. This study aims to analyze the trends and development patterns of metacognition research in physics education through a systematic review of the literature, identify the most researched aspects of metacognition as well as unanswered gaps in the context of physics education, and specifically assess effective metacognitive instructional practices or uncover the lack of research on teachers' pedagogical knowledge. This study examines 17 physics education- related papers that were published between 2013 to 2021 in peer-reviewed journals. Following data extraction based on the criteria introduced by Flavel, then synthesized and reported narratively. Based on the analysis, the findings of this study reported that the studies of metacognition in physics education focused on metacognitive knowledge (MK) more than metacognitive experience (ME), little attention has been given to metacognitive instruction in physics learning (n=7 out of 17 articles), and related to professional development of pre-service teachers (in higher education) and teachers of physics education, studies of metacognition for pre- and in-service trainings have not been addressed yet. These findings identified that there are gaps in research related to metacognition in physics education and these gaps need to be explored for further research. These findings identify that there are gaps in research relating to metacognition in physics education and these gaps need to be explored for further research. Thus, the results of this analysis are expected to provide a comprehensive mapping of the development of metacognition research in physics education, be the basis for the development of more effective learning strategies and metacognition-based teacher training, and open up further research opportunities, especially related to teacher pedagogical training and the integration of metacognition in the physics curriculum.